Cerebral Venous Thrombosis Developing after COVID-19 Vaccination: VITT, VATT, TTS, and More - Lippi, Giuseppe; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2021)
Despite the huge efforts globally underway for preventing or limiting the spread of severe acute respiratory coronavirus disease 2 (SARS-CoV-2), the coronavirus disease 2019 (COVID-19) pandemic outbreak appears still virtually unstoppable. As for many other infectious diseases, COVID-19 vaccination has now become crucial for limiting viral spread, especially for averting hospitalizations, need for intensive care, and fatal outcome. Nonetheless, as for other vaccines, COVID-19 vaccination is not completely free from side effects. Among the adverse events that have been reported after receiving COVID-19 vaccination, special emphasis has been given to an unexpected number of thrombocytopenic episodes with or without thrombotic complications, especially in recipients of adenovirus-based COVID-19 vaccines. Along with a specific clinical presentation, encompassing “atypical” thrombosis (especially cerebral venous [sinus] thrombosis, CVT) more prevalent in young female subjects, this new syndrome called vaccine-induced thrombocytopenia and thrombosis (VITT) is characterized by, and thereby diagnosed for, the presence of three paradigmatic laboratory abnormalities, i.e., low platelet count (<150 × 109/L), elevated plasma D-dimer levels (>0.5 mg/L), accompanied by a positive test for anti-PF4 (platelet factor 4) antibodies assayed with ELISA (enzyme-linked immunosorbent assay) techniques. Timely identification of these important abnormalities by both clinicians and laboratory professional is essential for early diagnosis and management of VITT, since the outcome of this condition may be fatal in half or even more of effected patients with severe disease. Therefore, this narrative review aims to review here the epidemiology, pathogenesis, clinical, and laboratory characteristics of VITT and other COVID-19 vaccine-associated thrombocytopenias.
Keywords: SARS-CoV-2; COVID-19; platelets; thrombosis; vaccine